RELIGIOUS COPING, RESILIENCE AND SPIRITUAL WELL-BEING AMONG WOMEN WITH BREAST CANCER; COMPARISON OF DIFFERENT AGE GROUPS AND DIFFERENT STAGES OF CANCER - Aman, Fizza; Akhtar, Nasreen (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out differences in the level of religious coping, resilience and spiritual well-being in young, middle aged and older patients with breast cancer. Methodology: This cross sectional survey was conducted on 60 women with breast cancer who were selected through purposive sampling technique. The age range of young participants was 20 to 35 years while that of middle age was 36 to 55 years and elderly were 56 to 70 years old. Connor-Davidson Resilience Scale, The Brief RCOPE Scale and Spiritual Index of Well-being were used for measuring the study variables. Results: Older women scored significantly higher on spiritual well-being (M=26.63, SD=10.22) than middle aged (M=21.08, SD=5.21), and young women (M=20.17, SD= 5.06). However, the three age groups did not differ significantly on religious coping, F (2, 57) = .90, p= 0.56 and resilience, F (2, 57) = 2.33, p= 0.10. Women passing through stage 2 of breast cancer used more religious coping (M=19.10, SD= 4.26) than those at stage 3 (M=16.85, SD= 3.36) and 4 (M=15.83, SD= 2.14). Moreover, these patients had higher resilience at stage 2 (M=29.50, SD=4.59) as compared to those at stage 3 (M=19.09, SD=7.81) and 4 (M=23.10, SD=9.30). Conclusion: Women at initial stage of breast cancer used more religious coping and resilience as compared to later stage. Moreover, older patients had higher spiritual wellbeing than young and middle-aged patients.